Gender differences in the mental health impact of the COVID-19 lockdown: Longitudinal evidence from the Netherlands - A. Vloo; R.J.M. Alessie; J.O. Mierau; Marike H. Boezen; Jochen O. Mierau; Lude Franke; Jackie Dekens; Patrick Deelen; Pauline Lanting; Judith M. Vonk; Ilja Nolte; Anil P.S. Ori; et al. (Elsevier, 2021)
Recent contributions highlighted gender differences in the mental health consequences of COVID-19 lockdowns. However, their cross-sectional designs cannot differentiate between pre-existing gender differences and differences induced by lockdowns. Estimating fixed-effects models using longitudinal data from the Lifelines biobank and cohort study with repeated mental health measurements throughout the lockdown, we overcome this caveat. Significant gender differences in mental health during the lockdown were found, where women experienced more depression symptoms and disorders and men experienced more anxiety symptoms and disorders stemming from the lockdown. Policymakers need to keep in mind that the COVID-19 lockdowns have different effects on mental health for men and women.